Clinico-Pathological Study of Phalatrikadi Ghana Vati and Vasadi Ghana Vati on Kamala w.s.r to Jaundice - Khuntia, Sandhyarani; Panda, Pradip Kumar; Sahu, Manoranjan; Biswas, Ashish (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Kamala, described in Ayurveda classics resembles to the clinical features of Jaundice. Liver i.e. Yakrita is the Moolasthana of Pachak Pittas, Raktavaha strotasa. Which we can correlate with Hepatobiliary system. Disturbance or diseases of hepatic system leads to mortality all the way through failure of remaining systems of our body. Kamala is one of the most important and specified disease of Yakrita which can be correlated with Jaundice. Materials and methods: A clinical study on 30 Kamala patients, (15 patients each in Group-A and Group-B) were registered from OPD and IPD of Govt. Ayurvedic College and Hospital, Balangir, Odisha. The patients presented with the Subjective Parameters of Haridra netra, twak, nakha and mukha (yellow discoloration of eye, skin, nail bed and oral mucosa), Rakta pita purisha and mutra, Bheka varna , Hatendriya, Daha , Avipaka Daurbalya, Sadana, Aruci, Karshana and Objective parameters as LFT, Urine Bile Salt/Bile Pigment, Stool examination and CBC were selected for clinical study. Group-A patients were treated with Phalatrikadi Ghana Vati (500mg) and Group-B patients with Vasadi Ghana Vati (500 mg) thrice daily after food with honey or luke warm water orally for 15 days respectively. The patients were assessed at 10 days interval up to 30 days in order to find the efficacy of both the trial drugs. The subjective and objective parameters were analysed statistically by Wilcoxon-W test and p-value. Observation and result: The Statistically significant (P<0.05) result was revealed in both Group-A and Group-B but improvement was noticed more in Group-A. Conclusion: -The overall study revealed that the trial on Phalatrikadi Ghana Vati, i.e., Group A showed more efficacy than Vasadi Ghanavati i.e, Group-B. The composition of Phalatrikadi Ghana Vati helped more to develop the body immunity as well as maintain the LFT parameters rather than Vasadi Ghanavati. No adverse effects was noticed during clinical trial in both groups.